The Effect of Dividend Policy on Firms Performance - Kashmiri, Mr. Rameez; Zada, Mr. Lal; Wadood, Dr. Falzi (The journal of contemporary issues in business and government, 2021)
The central aim of the study was to examine the effect of dividend policy on the firm financial performance of non-financial companies in Pakistan. Data was collected from the annual reports of non-financial companies listed on Pakistan Stock Exchange (PSX) for the period 2010 to 2015. Return on Assets (ROA) and Return on equity (ROE) were used to measure the firm‟s financial performance. Dividend Coverage Ratio (DCR), Dividend Payout Ratio (DPR) and Retention Ratios (RR) were used to calculate Dividend policy whereas debt to equity ratios were used to measure Capital Structure. For analyzing data the panel regression analysis method had been used as a statistical technique wherein a significant positive relationship was found between the firms „performance and the dividend policy, whereas the firm‟s size was in-significant to the firms‟ financial performance. The results showed no connection between capital structure and firm‟s financial performance. The results also showed a significant relation between firm‟s performance and Dividend policy. The firm‟s financial performance was not affected by Size. The second model has found significant impact of leverage on return on equity.